Meaning of Work and Employee Adaptation to Digital Transformation in SMEs in Makassar: A Phenomenological Study - Burhanuddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study examines how employees in small and medium-sized enterprises (SMEs) in Makassar, Indonesia, perceive the meaning of their work amid the accelerating digital transformation wave. Employing an interpretive phenomenological design, the research engaged 20 purposively selected participants through in-depth interviews to illuminate their lived experiences of adapting to new digital tools, evolving job roles, and heightened productivity demands. Thematic analysis produced five overarching themes: changing meaning of work (employees discovering renewed purpose through skill acquisition and personal development); digital adaptation (learning strategies and coping mechanisms for new technologies); productivity pressure (stress arising from accelerated work demands); organizational support (the role of training programs and managerial communication); and employee resilience (proactive and coping behaviors). Findings are situated within theories of work adjustment, technology acceptance, and work design. The study contributes to work psychology by demonstrating how SME workers actively reconstruct meaning and adapt during technological change. Managerial implications include prioritizing employee training, supporting work–life balance, and engaging workers in the formulation of digital strategy.